Unlocking Potential: Advancements and Applications in Prompt Engineering for NLP - Panjavani, Jatin Kumar (International Journal of Computer Sciences and Engineering, 2025)
The new area on prompt engineering throughout natural language processing (NLP) is investigated during the current article. It look at different approaches and strategies for creating prompts that maximize the functionality of big language models like GPT-4. The study outlines the importance of fast engineering in enhancing model outputs, talks about the difficulties encountered, and provides example studies showing effective implementations in various fields. NLP has evolved dramatically with the introduction on large language models (LLMs) similar GPT-4, which allow machines to produce text that is remarkably coherent and fluent, much like that of a human. However, the prompts that these models are given have a significant impact on how effective they are. The technique of creating and improving prompts to improve model performance, known as prompt engineering, has become a crucial field of study. This essay offers a thorough analysis regarding rapid engineering, looking at its methods, theoretical underpinnings, along with real-world applications. We begin by defining prompt engineering and contextualizing its importance within the broader landscape of NLP and AI. A thorough review of existing literature reveals various techniques and strategies for constructing effective prompts, including template-based approaches, prompt tuning, and the use of prompt-based transfer learning. The paper also addresses the challenges inherent in prompt engineering, such as managing ambiguity, mitigating bias, and ensuring scalability across different applications. Through detailed case studies, we illustrate the impact of prompt engineering on diverse domains, including education, healthcare, business, and creative industries. These examples demonstrate how tailored prompts will significantly boost the model outputs` quality and relevance, improving user experiences while streamlining workflows. Finally, the paper discusses future directions in prompt engineering research, highlighting the potential for automated prompt generation, integration with other AI technologies, and interdisciplinary applications. We can open up new avenues for AI-driven innovative thinking and problem-solving by improving our comprehension of and utilization of prompt engineering. This study emphasizes how important quick engineering can be for maximizing LLM capabilities advocating for continued investment in this field to address current challenges and explore new opportunities.